2023
DOI: 10.1038/s41598-023-33461-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of a damped harmonic forced duffing oscillator with time delay

Abstract: This paper is concerned with a time-delayed controller of a damped nonlinear excited Duffing oscillator (DO). Since time-delayed techniques have recently been the focus of numerous studies, the topic of this investigation is quite contemporary. Therefore, time delays of position and velocity are utilized to reduce the nonlinear oscillation of the model under consideration. A much supplementary precise approximate solution is achieved using an advanced Homotopy perturbation method (HPM). The temporal variation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Ref. [115] also establishes that for some specific combination of the system parameters, vibration amplitudes and harvested power can be amplified up to three or five times in comparison to the classical broadband nonlinear energy harvester based on the forced (kicked) Duffing oscillator (DO) [15,116,117]. A method to generate stability plots for the Mathieu equation in case of a toroidal ion trap mass analyser is presented in [118].…”
Section: Of 36mentioning
confidence: 99%
“…Ref. [115] also establishes that for some specific combination of the system parameters, vibration amplitudes and harvested power can be amplified up to three or five times in comparison to the classical broadband nonlinear energy harvester based on the forced (kicked) Duffing oscillator (DO) [15,116,117]. A method to generate stability plots for the Mathieu equation in case of a toroidal ion trap mass analyser is presented in [118].…”
Section: Of 36mentioning
confidence: 99%
“…Analytical approaches for nonlinear issues have garnered escalating interest among scientists and professionals in engineering due to the nonlinear sciences' rapid development during the past two decades. It was developed to study the behavior of these NLDEs using numerical and other approximation methods [6][7][8][9][10][11][12][13][14] . There have been a number of new techniques for finding analytical solutions to the NLDE recently.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Amongst other issues, the response of a Duffing oscillator (DO) [15,116] to a harmonic excitation, in presence of (viscous) damping, is known to exhibit hysteretic and chaotic behaviors [1,13,100,117,118]. It is demonstrated that in particular cases, the damping force may induce instability in the ion dynamics [119,120].…”
Section: Introductionmentioning
confidence: 99%